"It's too hard" - the management of latent TB in under-served populations in the UK: a qualitative study - Adam Thorburn Gray; Julian Surey; Hanif Esmail; Alistair Story; Magdalena Harris (BMC, 2022)
Abstract Background UK national guidance recommends systematic screening for latent tuberculosis infection (LTBI) in under-served populations, including people experiencing homelessness and people who use drugs. This is not routinely implemented in the UK, and the reasons for this policy-practice mismatch remain underexplored. Methods Semi-structured qualitative interviews were conducted with 19 healthcare professionals from across the UK. Participants were recruited using purposive sampling and snowballing, identifying individuals with excellent knowledge of their regions practice and policy of LTBI management. The interviews were conducted online, and were audio recorded, with transcripts thematically analysed using a two-stage inductive coding process to explore perceived barriers and enablers to LTBI screening. Results Most participants had previous experience managing LTBI in under-served populations, but none were conducting systematic screening as per national guidance. We identified service provision challenges and low prioritisation of LTBI as the key explanatory themes driving this policy-practice mismatch. Lack of resource, and the complexity of clinical decision making were two key service level barriers. System and service inertia, and lack of cost effectiveness evidence led to LTBI being deprioritised. Service integration and promotion of WHO targets for TB elimination were highlighted as potential solutions. Conclusion Integrating LTBI testing and treatment with existing health services for under-served populations could improve feasibility and efficacy. Promotion of UK TB elimination goals and generation of regional evidence to support commissioning for LTBI care is vital. Without such a multi-pronged approach inertia is likely to persist and the zeitgeist will remain: "it's too hard".